Outcome of Extracranial Carotid Pseudoaneurysm Surgery: A Retrospective Study - Bhandari, Nikesh; Shrestha, Uttam K; Shrestha, Kajan R; Gurung, Dinesh (Journal of Institute of Medicine Nepal, 2020)
Introduction Extracranial carotid pseudoaneurysm (ECPA) is commonly associated with blunt or penetrating trauma and can result in thromboembolic event, cranial nerves palsies, rupture and hemorrhage. Due to the limited number of large studies, safety and efficacy of surgical and interventional management of ECPA is not well characterized. Open surgery with resection of pseudoaneurysm with end-to-end anastomosis or interposition graft is currently the preferred method of management. The aim of this study is to study the demographics, etiopathogenesis, presentation and outcome after surgical intervention of ECPA at our center. Methods All patients who underwent surgery for carotid pseudoaneurysm form June 2012 to December 2019, at Department of Cardiothoracic and Vascular Surgery were included in this retrospective chart review study after evaluation of the hospital record book and electronic medical record. Patients who had stroke or cranial nerve injury before surgery, were excluded from this study. Results Fifteen patients met the inclusion criteria. Male to female ratio was 11:4. Mean age of presentation was 38.17±18.98 years. All patients presented with tender and pulsatile neck swelling. Common carotid artery involvement was more common. Three patients suffered from stroke postoperatively, and all of these patients died, however, one patient with stroke died due to reasons not related to pseudoaneurysm. Two patients suffered cranial nerve injury and ten patients had no other disabling complications. Conclusion ECPA is an uncommon but a serious disease and ischemic stroke after surgery is associated with high mortality.